P160 What impact did the xx commonwealth games have on stis and sexual health services in glasgow?. (18th May 2015) - Acquah, Rebecca; Metcalfe, Rebecca; Winter, Andrew
Abstract : Background/introduction: An estimated 600, 000 spectators, volunteers and athletes from over 70 countries visited Glasgow for the XX Commonwealth Games, held between 23 July and 3 August 2014, doubling the city's population. Aim(s)/objectives: We sought to investigate the impact of the Games on the number of acute STIs and on service activity in core specialist sexual health services, which offer free walk-in access. Methods: We interrogated our city-wide electronic patient record system (NaSH) to measure service activity, the number of acute STIs and PEPSE prescriptions between the 9 th July and the 31 st August 2014. We compared these to the same time period in 2013. We prospectively asked all new clinic attendees if they were in Glasgow for the Games. Results: Of the 1496 attendees who responded, just 1.7% (26) were in Glasgow solely for the Games. Discussion/conclusion: Despite the huge influx of visitors, service activity and overall acute symptomatic STI incidence decreased by around 10% during and after the Games compared to 2013. We found no evidence that large sporting events increase demand for sexual health services or cause a rise in acute STIs.